Establishment of a dual mode immunochromatographic assay for Campylobacter jejuni detection - He, Deyun; Wu, Zhengzong; Cui, Bo; Xu, Enbo; Jin, Zhengyu (Food chemistry, 2019)
•We proposed a dual mode lateral flow assay for the detection of Campylobacter jejuni.•The novel assay was based on colorimetric and spectroscopic properties of AuNR@Pt.•This assay possesses low detection limit and wide linear range. Campylobacter jejuni (C. jejuni) is considered one of the most common cause of human gastroenteritis. Aiming to detect C. jejuni in food products rapidly and sensitively, a dual mode lateral flow assay, based on the peroxidase mimicking and surface enhanced Raman scattering (SERS) enhancement properties of platinum coated gold nanorods (AuNR@Pt), was developed in this study. Under color mode and SERS mode, the proposed assay showed good linear response in the range of 102–106 cfu/mL and 102–5 × 106 cfu/mL with limits of detection of 75 cfu/mL and 50 cfu/mL, respectively (S/N = 3). Furthermore, the reliability of the dual-readout lateral flow assay (LFA) was successfully demonstrated by the application on milk samples, in which the recoveries ranged from 89.33% to 107.62%. Overall, the immunochromatographic assay developed in this work is promising and has good chance to be employed for sensitive detection of C. jejuni in food products.